1995
DOI: 10.1097/00005392-199509000-00106
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Muscarinic M sub 3 -Receptors Coupled to Inositol Phospholipid Hydrolysis in Human Detrusor Cultured Smooth Muscle Cells

Abstract: These results indicate that human detrusor smooth muscle cells in culture express M3 muscarinic receptors which are linked to phosphoinositide hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 0 publications
0
34
0
3
Order By: Relevance
“…Reported affinity ranges for the M2 subtype is shaded with horizontal lines, and reported affinity for the M3 subtype is shaded with vertical lines. Symbols refer to the affinities that were determined by Schild analysis of the bladder tissue obtained from the individual patient numbers indicated in Table 1. muscle cells have demonstrated greater numbers of M 2 than M 3 receptors (27,28,32,33,39). The mRNA encoding M 2 and M 3 has been reported to be present in equal amounts (50).…”
Section: Discussionmentioning
confidence: 99%
“…Reported affinity ranges for the M2 subtype is shaded with horizontal lines, and reported affinity for the M3 subtype is shaded with vertical lines. Symbols refer to the affinities that were determined by Schild analysis of the bladder tissue obtained from the individual patient numbers indicated in Table 1. muscle cells have demonstrated greater numbers of M 2 than M 3 receptors (27,28,32,33,39). The mRNA encoding M 2 and M 3 has been reported to be present in equal amounts (50).…”
Section: Discussionmentioning
confidence: 99%
“…These regulatory actions are mediated through the interaction of norepinephrine (sympathetic component released by hypogastric nerve stimulation), acetylcholine and ATP (parasympathetic components released by pelvic nerve stimulation) with adrenergic, muscarinic and purinergic receptors, respectively [2]. Stimulation of M 2 and M 3 muscarinic receptors produce detrusor smooth muscle contraction [4][5][6][7], whereas sympathetic activation of post-junctional α 1 -adrenoceptors in the urethra and bladder trigone plays a key role in the maintenance of urethral closure pressure [4,[8][9][10]. In addition, β 2 -and β 3 -adrenoceptors mediate relaxation of rat and human detrusor, causing bladder activity inhibition [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a predominance of m 2 receptors in human and animal detrusor, several investigators have found that the pharmacologically defined M 3 receptor mediates bladder contraction [7]. Cultured human detrusor cells expressed M 3 receptors linked to phosphoinositide hydrolysis [13]. Recently, however, also M 2 receptors were shown to be able to mediate rat bladder contraction in vitro as well as in vivo by reversing β-adrenoceptor-mediated relaxation [16].…”
Section: Bladdermentioning
confidence: 99%